Monitoring the security system at pistol storage based on a web server in army units - Imam Farhan Santoso; Heri Setiawan; Aguk Sridaryono; Dekki Widiatmoko; Kasiyanto (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
The employment of security features is crucial to the operation of many modern electronic gadgets in the current 5.0 era as time and technology advance. This means that we must keep coming up with new ideas and producing instruments that will enhance security. Among the many issues that come up is the fact that guns are still registered, checked out, and returned using public books, which leaves space for data tampering or the chance that the books are lost. The primary goal of this research is to create and execute a web-based system that uses fingerprints to monitor the borrowing and return of firearms. Because of its nature online-his, this system will streamline operations and enable users to conveniently view inventory from any location. Researchers employ literature methodology, which includes reading, debating, synthesizing, and developing the concepts employed, in addition to employing laboratory techniques and the necessary tools to accomplish their objectives. The web server on which the security monitoring system for keeping firearms is based has undergone extensive testing and analysis, and the findings indicate that generally, the device can operate as intended. This conclusion is based on traffic analysis and access patterns on the web server. Following the completion of five tests with a 95% accuracy rate. Finally, the security monitoring system for the storage of firearms is based on a web server and has undergone extensive testing and analysis with a 90% speed and accuracy rate; the findings indicate that, on the whole, the instrument can perform as intended